Comparison of singleplex and multiplex Real-Time Reverse Transcription – Polymerase Chain Reaction for the detection of Severe acute respiratory syndrome Coronavirus 2 - Monteiro, Francielle Liz; Volpato, Fabiana Caroline Zempulski; Wink, Priscila Lamb; Willig, Julia Biz; Paiva, Rodrigo Minuto; De-Paris, Fernanda; Mozzaquatro, Rafaela Bianchin; Barth, Afonso Luis (Disciplinarum Scientia | Saúde, 2023)
The main laboratorial test for the diagnosis of COVID-19 (Coronavirus disease 2019) is the detection of SARS-CoV-2 (Severe acute respiratory syndrome coronavirus 2) RNA by the RT-qPCR (real-time reverse transcription - polymerase chain reaction) technique. To optimize the diagnosis of COVID-19, we have developed a multiplex real-time reverse transcription polymerase chain reaction (RT-qPCR) technique, which targets the nucleocapsid protein of SARS-CoV-2. The multiplex RT-qPCR assay was compared with the US CDC singleplex protocol. Protocol 1 included 113 RNA samples previously tested for SARS-CoV-2 and Protocol 2, included 107 fresh RNA samples that were tested simultaneously by the singleplex and multiplex. Protocols 1 and 2 presented agreement between singleplex and multiplex RT-qPCR of 88.5% and 98,1%, respectively. After the validation of the multiplex RT-qPCR assay, this methodology was applied in the routine of the diagnostic laboratory and 2,015 samples were analyzed in the first month of the multiplex use. In this period, we found that the multiplex assay proved to be a practical approach which provided reliable results. In conclusion, the multiplex RT-qPCR using primers for targets N1 and N2 is comparable to singleplex.